TruFit Plug for Repair of Osteochondral Defects—Where Is the Evidence? Systematic Review of Literature. (January 2015) - Verhaegen, J.; Clockaerts, S.; Van Osch, G.J.V.M.; Somville, J.; Verdonk, P.; Mertens, P.
Objective: Treatment of osteochondral defects remains a challenge in orthopedic surgery. The TruFit plug has been investigated as a potential treatment method for osteochondral defects. This is a biphasic scaffold designed to stimulate cartilage and subchondral bone formation. The aim of this study is to investigate clinical, radiological, and histological efficacy of the TruFit plug in restoring osteochondral defects in the joint. Design: We performed a systematic search in five databases for clinical trials in which patients were treated with a TruFit plug for osteochondral defects. Studies had to report clinical, radiological, or histological outcome data. Quality of the included studies was assessed. Results: Five studies describe clinical results, all indicating improvement at follow-up of 12 months compared to preoperative status. However, two studies reporting longer follow-up show deterioration of early improvement. Radiological evaluation indicates favorable MRI findings regarding filling of the defect and incorporation with adjacent cartilage at 24 months follow-up, but conflicting evidence exists on the properties of the newly formed overlying cartilage surface. None of the included studies showed evidence for bone ingrowth. The few histological data available confirmed these results. Conclusion: There are no data available that support superiority or equality of TruFit compared to conservative treatment or mosaicplasty/microfracture. Further investigation is needed to improve synthetic biphasic implants as therapy for osteochondral lesions. Randomized controlled clinical trials comparing TruFit plugs with an established treatment method are needed before further clinical use can be supported.